2014
DOI: 10.1371/journal.pone.0103281
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C-Type Lectin Receptors MCL and DCIR in Experimental Colitis

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gastrointestinal tract. Though its exact etiology is still unclear, it is proposed that an imbalance in the intestinal homeostasis leads to a disturbed interaction between commensal microbiota and the mucosal immune system. Previous studies have shown that both innate and adaptive immunity are involved in an overwhelming colon inflammation, and thus contribute to the pathogenesis of IBD. In innate immunity, several pattern recognition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…It is well established that switching of C. albicans from yeast to hypha is crucial for tissue invasion, and that glycans expressed on the surface of C. albicans are crucial for proper recognition and response by epithelial cells mostly via recognition by TLRs and C‐type lectin receptors . Here we demonstrate a clear upregulation of TLR2 and TLR4 in epithelial cells and T cells, upon stimulation with yeast and hypha, suggesting a possible mode of action for fungal recognition.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is well established that switching of C. albicans from yeast to hypha is crucial for tissue invasion, and that glycans expressed on the surface of C. albicans are crucial for proper recognition and response by epithelial cells mostly via recognition by TLRs and C‐type lectin receptors . Here we demonstrate a clear upregulation of TLR2 and TLR4 in epithelial cells and T cells, upon stimulation with yeast and hypha, suggesting a possible mode of action for fungal recognition.…”
Section: Discussionsupporting
confidence: 52%
“…Possible candidates for fungal recognition by adaptive cells could be C‐type lectin receptors , DC‐SIGN , mannose receptor , or galectins . Recently, C‐type lectin receptors have been suggested to initiate intestinal inflammation in both humans and mice , via fungal recognition and act as adjuvants to stimulate both the innate and adaptive immune reaction. Noteworthy, we used soluble laminarin.…”
Section: Discussionmentioning
confidence: 99%
“…The APLEC gene cluster is also associated with motor neuron survival after traumatic nerve root injury (Lindblom et al, 2013). In knockout mice, these different receptor genes have been linked to the development of arthritis (Fujikado et al, 2008), to experimental colitis (Hütter et al, 2014; Tokieda et al, 2015) and to EAE, as well as being involved in the response to infection (Uto et al, 2016). Further studies are needed to better understand how the APLEC region is involved in immune regulation and in inflammation in humans.…”
Section: Different Strategies Of Disease Gene Identificationmentioning
confidence: 99%
“…Mice lacking this molecule develop more severe inflammation after DSS‐treatment, accompanied with impaired IL‐10 secretion . Although MCL and DCIR also bind some intestinal commensal microbiota, mice deficient in these molecules develop slightly more severe DSS–induced colitis . Another report showed that DCIR‐deficient mice develop even milder colitis, with reduced neutrophil‐attracting chemokine MIP‐2 and decreased accumulation of neutrophils .…”
Section: Myeloid Clrs In Intestinal Mucosal Immunitymentioning
confidence: 99%